Latent Profile Analysis to Survey Positive Mental Health and Well-Being: A Pilot Investigation Insight Tunisian Facebook Users - Guelmami, Noomen; Tannoubi, Amayra; Chalghaf, Nasr; Saidane, Mouna; Kong, Jude; Puce, Luca; Fairouz, Azaiez; Bragazzi, Nicola Luigi; Alroobaea, Roobaea (Frontiers in Psychiatry, 2022)
Background: To examine mental health during COVID-19 peaks, lockdown, and times of curfew, many studies have used the LPA / LCA person-centred approach to uncover and explore unobserved groups. However, the majority of research has focused only on negative psychological concepts to explain mental health. In this paper, we take another perspective to explore mental health. In addition, the study focuses on a period of peak decline in the COVID-19 pandemic. Objective: The present paper aim (1) to identify latent profiles from several parameters related to positive psychology among Internet users and (2) to compare profiles by sociodemographic variables. Methods: Cross-sectional data were collected through an online survey among 950 participants were female (n=499; 52.53%) and male (n=451; 47.47) with an average age =31.30±9.42. Subjects filled Arabic version of the Satisfaction with Life Scale, Scale of Happiness, Gratitude Questionnaire, International Physical Activity Questionnaire (IPAQ), and the Spiritual Well-Being Scale. Results: The LPA results revealed three clusters. The first cluster (n=489, 51,47%) contains individuals who have low scores on the positive psychology scales. The second cluster (n=357, 37,58%) contained individuals with moderate positive psychology scores. However, a third cluster (n=104, 10,95%) had high positive psychology scores. The selected variables in the model were put to a comparison test to ensure that the classification solution was adequate. Subsequently, the clusters were compared for the variables of socio-demographics, use of the internet for entertainment and physical activity, the results showed significant differences for gender (low mental well-being for the female gender), socio-economic level (low for the low-income class), and physical activity (low mental well-being for the non-exerciser). However, no significant differences were found for the variables age, location, and use of the Internet for entertainment. Conclusion: Our results complement person-centered studies (LPA/LCA) related to the COVID-19 pandemic and can serve researchers and mental health practitioners in both diagnostic and intervention phases for the public. In addition, the GQ6 scale can be administered to measure gratitude for culturally similar populations.